The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fonc.2022.621460
|View full text |Cite
|
Sign up to set email alerts
|

The Profiles of Tet-Mediated DNA Hydroxymethylation in Human Gliomas

Abstract: Gliomas are the most common primary malignant intracranial brain tumors. Their proliferative and invasive behavior is controlled by various epigenetic mechanisms. 5-hydroxymethylcytosine (5-hmC) is one of the epigenetic DNA modifications that employs ten-eleven translocation (TET) enzymes to its oxidation. Previous studies demonstrated altered expression of 5-hmC across gliomagenesis. However, its contribution to the initiation and progression of human gliomas still remains unknown. To characterize the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Demethylation is the process of oxidative conversion of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) by the so-called ten-eleven translocase enzymes (TETs). Reduced expression of TET enzymes and a decrease in 5hmC levels have been described in gliomas, with the reduction being much more pronounced in glioblastomas than in gliomas with a lower tumor grade [ 172 , 173 ]. Ascorbate, a cofactor of TET enzymes, was also significantly reduced in gliomas, with significantly lower levels in glioblastomas [ 173 ].…”
Section: Discussionmentioning
confidence: 99%
“…Demethylation is the process of oxidative conversion of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) by the so-called ten-eleven translocase enzymes (TETs). Reduced expression of TET enzymes and a decrease in 5hmC levels have been described in gliomas, with the reduction being much more pronounced in glioblastomas than in gliomas with a lower tumor grade [ 172 , 173 ]. Ascorbate, a cofactor of TET enzymes, was also significantly reduced in gliomas, with significantly lower levels in glioblastomas [ 173 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pHGG such as GBM, an oncometabolite, 2‐hydroxy glutarate which accumulates due to the mutation of IDH gene, affects the structure of chromatin by altering epigenetic variables such as histone post‐translational modification and global DNA methylation. This impairment leads to the inhibition of ten‐eleven translocation ( TET )‐mediated demethylation leading to hypermethylation in the cells and as a result, a drop in patient survival was observed 118 . Other non‐recurrent epigenetic mutations found in pA include chromodomain helicase DNA‐binding proteins, lysine‐specific demethylase, polycomb repressive complex 2, histone deacetylase 2, histone‐lysine N‐methyltransferase enzyme ( EZH2 and SET2 ), histone demethylase ( JARID1C ) and H3 K4 mono‐methyltransferase ( MLL2 ) 114 .…”
Section: Recent Clinical Advances In Epigenetic Alterationsmentioning
confidence: 99%
“…This impairment leads to the inhibition of ten‐eleven translocation ( TET )‐mediated demethylation leading to hypermethylation in the cells and as a result, a drop in patient survival was observed. 118 Other non‐recurrent epigenetic mutations found in pA include chromodomain helicase DNA‐binding proteins, lysine‐specific demethylase, polycomb repressive complex 2, histone deacetylase 2, histone‐lysine N‐methyltransferase enzyme ( EZH2 and SET2 ), histone demethylase ( JARID1C ) and H3 K4 mono‐methyltransferase ( MLL2 ). 114 In addition, other methylation markers in pA include genes involved in WNT signalling pathway such as secreted frizzled related protein (SFRP) group of proteins, those involved in STAT signalling pathway such as RASSF (Ras association domain family member), those involved in cell migration, proliferation and apoptosis such as slit guidance ligand 2 ( SLIT2 ), epithelial membrane protein 3 ( EMP3 ) and receptor for RANK‐ligand ( RANK ), respectively.…”
Section: Recent Clinical Advances In Epigenetic Alterationsmentioning
confidence: 99%
“…the pathogenesis of gliomas(Bragiel-Pieczonka et al 2022).Chen et al showed the glioma grade advanced as the TET2 expression decreased partially due to Zinc finger E-box-binding homeobox 1 in non-stem-like cell GBM models(Chen et al 2017). When concerning TET2 involvement in lymphoid and myeloid cell development and its functional roles, we discussed how TET2 activities are modulated by microRNAs.…”
mentioning
confidence: 95%